The Impact of Leadership Roles on Team Satisfaction, Team Effectiveness and Project Performance – A Study of Project Managers in Malaysia - Fung, Han Ping; Ramasamy, Shamala (AeU, 2015)
Many organizations today are deploying project teams to deliver various services or resolve different problems as they recognize the team performance is always exceeding the individual outputs combined. According to Project Management Institute (PMI) (2013), project manager’s leadership skills are deemed important as they contribute to achieving the project goals set by the stakeholders. However, there is a lack of study that examines whether a project manager’s leadership roles can improve team satisfaction, team effectiveness and project performance concurrently (Cohen & Bailey, 1997) or following a certain pattern of dependencies. In light of addressing these concerns, this study developed a research model based on research works conducted by Cohen and Bailey (1997), as well as by Yukl (2010) to empirically analyze how leadership roles influence team satisfaction, team effectiveness and project performance. Result showed that when a project manager demonstrates his or her leadership roles more frequently, the project team becomes more effective. Increase in team effectiveness leads to higher team satisfaction and improved project performance. Moreover, when the project team becomes more satisfied, it will also directly increase project performance. However, execution of the leadership roles by project manager will not directly influence the team satisfaction and project performance.